Klasifikasi User Berdasarkan Trafik Http/Https Menggunakan Metode Naïve Bayes - Prayoga, Eko; Diansyah, T.M; Liza, Risko (Algoritma: Jurnal Ilmu Komputer dan Informatika, 2023)
Along with the times and accompanied by advances in information and communication technology, it is undeniable that at this time all activities use information technology. One of the activities is to use the internet. The research will conduct a classification based on internet usage data obtained through questionnaires using data mining techniques. The attributes that will be used in doing the classification are Name, Age, Gender, Last Education. The method used is the Naïve Bayes method, which is one of the classification techniques in data mining. Based on the research conducted, it was concluded that based on internet user data used as training data, the Naïve Bayes method succeeded in classifying 32 data from 50 data tested. So the Naïve Bayes method succeeded in predicting the magnitude of the percentage of accuracy by 64%. Keywords : Data Mining, Classification, Naïve Bayes